Aircraft Noise and Land Use Zoning Compatibility around the Juan Santamaría Airport, Costa Rica - Rivera Acevedo, José Miguel (2020)
The purpose of this study is to evaluate the noise generated by aeronautical operations around Juan Santamaría Airport and its compatibility with the land use and the proposed zoning around the airport. Aircraft noise can produce discomfort, interference with daily activities, and excessive vibrations; hence, land use planning around airports is of importance. Maps were prepared through computational models representing the noise levels generated by the operations of the airport. The operations were analyzed by aircraft type, schedules, and flight tracks, for 2013 and projections for: 2016, 2026, and 2036. Noise level data were collected with a sound level meter at 28 points surrounding the airport. Comparing the annual maps of 2013 and 2036 it was determined that 41,24 % of the analyzed area will present clearly perceivable increases (5 dB(A) to 10 dB(A)), and 1,36 % of the area will have double loudness increases (10 dB(A) to 14 dB(A)). The 2016 maps show locations where it is recommended to incorporate solutions in the construction regulation that reduce between 25 dB and 30 dB in the residential and scholar areas located within 65 dB(A) and 70 dB(A), such as Coco, Rincón Monge, Rincón Herrera, and Bajo Sorda. This finding is supported by field measurements. The proposed zoning was contrasted against the yearly day-night average sound level of 2036. The biggest issue of excessive aircraft noise is located near the west runway where a range above the 75 dB(A) is expected. Any edification of permanent residence must be banned in here.